T. marneffei infection complications in an HIV-negative patient with pre-existing pulmonary sarcoidosis: a rare case report - Xiaoming Yu; Keji Miao; Changsheng Zhou; Yuelin Cai; Xiaoying Huang; Yanfan Chen; Mayun Chen; Hui Cai; Lin Zhang (BMC Infectious Diseases, 2018)
Abstract Background Talaromyces marneffei (T. marneffei) is a thermal dimorphic pathogenic fungus that often causes fatal opportunistic infections in human immunodeficiency virus (HIV)-infected patients. Although T. marneffei-infected cases have been increasingly reported among non-HIV-infected patients in recent years, no cases of T. marneffei infection have been reported in pulmonary sarcoidosis patients. In this case, we describe a T. marneffei infection in an HIV-negative patient diagnosed with pulmonary sarcoidosis. Case presentation A 41-year-old Chinese man who had pre-existing pulmonary sarcoidosis presented with daily hyperpyrexia and cough. Following a fungal culture from bronchoalveolar lavage (BAL), the patient was diagnosed with T. marneffei infection. A high-resolution computed tomography (HRCT) chest scan revealed bilateral lung diffuse miliary nodules, multiple patchy exudative shadows in the bilateral superior lobes and right inferior lobes, air bronchogram in the consolidation of the right superior lobe, multiple hilar and mediastinal lymphadenopathies and local pleural thickening. After 3 mos of antifungal therapy, the patient’s pulmonary symptoms rapidly disappeared, and the physical condition improved markedly. A subsequent CT re-examination demonstrated that foci were absorbed remarkably after treatment. The patient is receiving follow-up therapy and assessment for a cure. Conclusion This case suggested that clinicians should pay more attention to non-HIV-related lung infections in patients with pulmonary sarcoidosis. Early diagnosis and treatment with antifungal therapy can improve the prognosis of T. marneffei infection.